Penerapan Hygiene dan Sanitasi pada Yulfia Catering di Mojoketo - Ayu Rahmawati Dewi; Niken Purwidiani; Asrul Bahar; Ita Fatkhur Romadhoni (Pusat Riset dan Inovasi Nasional, 2024)
The research objective of this final assignment is to describe the implementation of hygiene, sanitation and catering at Yulfia Catering in Mojokerto. This research uses theories from experts who study the implementation of hygiene, sanitation and catering. The method used in this research is a qualitative method with a descriptive approach. This research uses more interview and documentation techniques to support a qualitative approach. This research uses many data collection techniques using interviews and documentation. The focus of this research is to determine the implementation of hygiene, sanitation and catering carried out at Yulfia Catering Mojokerto. The final results of this research indicate that Yulfia Catering in Mojokerto needs follow-up regarding an efficient work system in dealing with consumers during busy times. Because when orders are busy, hygiene and sanitation are sometimes ignored.